STRATEGI DAN KINERJA DALAM SISTEM KOMPENSASI - Mimin Nur Aisyah (Jurnal Pendidikan Akuntansi Indonesia, 2006)
Compensation system has been broadly discussed because of its significant role in enhancing productivity dan performance. It able to motivate a goal directed behavior. Compensation system is expected to provide organizational goal congruence. There are several norms that will lead to different reward distribution. In determining what compensation system that should be taken, organization should consider these dimensions: (1) short term vs long term, (2) cash vs equity, and (3) monetary vs non monetary. Strategy and performance play important role in organizational compensation system. Empirical evidences had support the relation between company’s strategy and its incentive system. Strategic orientation has significant effect on incentive system. To intervene the gap between what is actually needed from compensation system and its practices, the design of reward system should be improved through: (1) give reward to managers only if they perform better than competitors, (2) determine the contribution of each business unit to company stock price, and (3) involve the contribution of front line manager and employees in achieving higher shareholder values. Theory has supports the effectiveness of compensation system, but some evidences showed the contrary. The failness of incentive plans to motivate long term performance should drive the organization to improve the design and implementation of the existed system or to create a new and more effective incentive system.